MODELING OF INFORMATION SECURITY SYSTEM IN COMPUTER NETWORK (Information systems and technologies security, 2019)
This article presents simulation modeling process as the way to studythe behavior of the Information Security system. Graphical Network Simulator isused for modeling such system and Kali Linux is used for penetration testing andsecurity audit. To implement the project GNS3 package is selected. GNS3 is agraphical network emulator that allows you to simulate a virtual network ofmore than 20 different manufacturers on a local computer, connect a virtualnetwork to a real one, add a full computer to the network, Third-partyApplications for network packet analysis are supported. Depending on thehardware platform on which GNS3 will be used, it is possible to build complexprojects consisting of routers Cisco, Cisco ASA, Juniper, as well as serversrunning network operating systems. Using modeling in the design of computingsystems, you can: estimate the bandwidth of the network and its components;identify vulnerability in the structure of computing system; compare differentorganizations of a computing system; make a perspective development forecastfor computer system; predict future requirements for network bandwidth;estimate the performance and the required number of servers in the network;compare various options for computing system upgrading; estimate the impact ofsoftware upgrades, workstations or servers power, network protocols changes onthe computing system. Research computing system parameters with differentcharacteristics of the individual components allows us to select the network andcomputing equipment, taking into account its performance, quality of service,reliability and cost. As the cost of a single port in active network equipment canvary depends on the manufacturer's equipment, technology used, reliability,manageability. The modeling can minimize the cost of equipment for thecomputing system. The modeling becomes effective when the number ofworkstations is 50-100, and when it more than 300, the total savings could reach30-40% of project cost.
Keywords: model; modeling; simulation; security; threats